Perelomov A. Рragmatics in business-communication - Perelomov A. (Philological Treatises, 2020)
The article deals with the contemporary business-communication in its pragmatic aspect. We try to analyze some of the factors, which may influence the formation of pragmatics in the sphere of business communication, including all the levels of communication.